Exposure to cow’s milk as a prognostic factor for atopic dermatitis during the first three months of life - Putu Ayu Widyanti; Ketut Dewi Kumara Wati; Endy P. Prawirohartono (Paediatrica Indonesiana, 2014)
Background The incidence of atopic dermatitis has increased inthe early life of children. Cow's milk, the first foreign protein towhich infants are exposed, is predicted to be a prognostic factorof atopic dermatitis.Objective To determine if exposure to cow's milk is a prognosticfactor for atopic dermatitis during the first three months oflife.Methods We performed a cohort study involving 136 newbornsfrom families with and without histories of atopy in SanglahHospital, Denpasar, between April to August 20 12. Subjects wereallocated into 2 groups, those who were exposed to cow's milk(n=68) and not exposed to cow's milk (n=68). We analyzedthe impact of several possible prognostic variables on atopicdermatitis at 3 months of age including exposure to cow's milk,birth weight, sex, gestational age, exposure to cigarette smoke,early solid feeding, and history of atopy in the mother, the father,or both, as well as maternal consumption of chicken eggs whennursing. Data were analyzed with Cox's proportional hazardfunction. The cumulative incidence and incidence rate in eachgroup were calculated.Results Exposure to cow's milk in the first 3 months of liferesulted in a cumulative incidence of atopic dermatitis of 17 .6%,with an incidence rate of atopic dermatitis of 54.5%. However,multivariate analysis showed that cow's milk exposure was nota significant prognostic factor for atopic dermatitis (HR 1.3 7;95%CI 0.22 to 8.43).Conclusion Cow's milk exposure is not a prognostic factor ofatopic dermatitis during the first three months of life